1997
DOI: 10.1007/s004010050733
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of α1-syntrophin and neuronal nitric oxide synthase in normal skeletal myofiber, and their relation to each other and to dystrophin

Abstract: We investigated the ultrastructural localization of alpha 1-syntrophin and neuronal nitric oxide synthase (nNOS) in normal human skeletal myofibers and analyzed their relation to each other and to dystrophin using single and double immunogold-labeling electron microscopy. Single immunolabeling showed antibodies to alpha 1-syntrophin and nNOS on the inner surface of the muscle plasma membrane, the sarcoplasmic side of plasma membrane invaginations, and the sarcoplasm near mitochondria of subsarcolemmal areas. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…NO is a very small, freely diffusible, and ubiquitous molecule produced constitutively at high levels in muscle by neuronal nitric oxide synthase (NOS-I) (Nakane et al, 1993;Kobzik et al, 1994;Silvagno et al, 1996). NOS-I is complexed at its N terminus to ␣1-syntrophin, which, in turn, is linked to the dystrophin cytoskeleton, especially in fasttwitch fibers; in dystrophic muscles without dystrophin, NOS-I is reduced and displaced to the cytoplasm (Brenman et al, 1995Chang et al, 1996;Chao et al, 1996;Grozdanovic et al, 1996;Wakayama et al, 1997;Hemler, 1999). NO is also made constitutively by NOS-III and by inducible NOS-II activity and transduces signals in vascular endothelium and smooth muscle, brain, and liver.…”
Section: Introductionmentioning
confidence: 99%
“…NO is a very small, freely diffusible, and ubiquitous molecule produced constitutively at high levels in muscle by neuronal nitric oxide synthase (NOS-I) (Nakane et al, 1993;Kobzik et al, 1994;Silvagno et al, 1996). NOS-I is complexed at its N terminus to ␣1-syntrophin, which, in turn, is linked to the dystrophin cytoskeleton, especially in fasttwitch fibers; in dystrophic muscles without dystrophin, NOS-I is reduced and displaced to the cytoplasm (Brenman et al, 1995Chang et al, 1996;Chao et al, 1996;Grozdanovic et al, 1996;Wakayama et al, 1997;Hemler, 1999). NO is also made constitutively by NOS-III and by inducible NOS-II activity and transduces signals in vascular endothelium and smooth muscle, brain, and liver.…”
Section: Introductionmentioning
confidence: 99%
“…These findings imply that nNOS molecule associates with dystrophin molecule directly or indirectly. Our previous ultrastructural studies confirmed the close association of ␣1-syntrophin and nNOS (Wakayama et al, 1997). Very recently, Kameya et al (1999) generated ␣1-syntrophin knock-out mice that lacked nNOS immunoreactivity in the sarcolemma region of skeletal muscle.…”
Section: Discussionmentioning
confidence: 52%
“…In skeletal muscle, NO acts as a signaling molecule that is released from the dystrophin-glycoprotein complex and is involved in the regulation of myocyte development (Lee et al, 1994;Wang et al, 1995), acetylcholine receptor function at the neuromuscular junction (Wang et al, 1995), and muscle contractility (Kobzik et al, 1994). In skeletal muscle, NO is generated by nNOS, which is found at the myofiber periphery (Frandsen et al, 1996;Grozdanovic et al, 1995;Kobzik et al, 1994) when stained sections of skeletal muscle are examined with the light microscope, and is located close to the cytoplasmic face of the muscle plasma membrane (Wakayama et al, 1997) when studied with the electron microscope.…”
Section: Discussionmentioning
confidence: 98%
“…This pattern of nNOS distribution is invariably found in skeletal muscles of both myotome and branchial arch origin (Grozdanovic et al, 1995). By electron microscopy, Wakayama et al (1997) have detected nNOS at the inner surface of the sarcolemma, where it clusters in the costameres, as well as in subsarcolemmal areas near mitochondria, which may actually represent caveolae (see below).…”
Section: Nnos Is Lozalized At the Sarcolemma Of Extrafusal And Intrafmentioning
confidence: 94%